Bartonella endocarditis masquerading as systemic vasculitis with rapidly progressive glomerulonephritis (aka 'Löhlein nephritis'). Issue 12 (3rd December 2019) - Bannon, Lian; Choshen, Guy; Giladi, Michael; Ablin, Jacob
Abstract : Bartonella species are fastidious, Gram-negative aerobic rods and a well-recognised pathogen responsible for culture-negative endocarditis. The histopathological appearance of glomerulonephritis (GN) caused by Bartonella endocarditis may include a pauci-immune GN similar to that usually seen in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis. Herein, we present an unusual case report of Bartonella endocarditis masquerading as ANCA-positive vasculitis, with crescentic GN. A 66-year-old woman, who had undergone aortic valve replacement 2 years prior to admission, presented with confusion and loss of vision in her right nasal field. Following an extensive diagnostic evaluation, the main findings were right central retinal artery occlusion, ground-glass appearance on chest CT and ANCA-positive, anti PR-3 negative, rapidly progressive GN. The patient was scheduled to start treatment with rituximab for presumed ANCA-positive GN, when a positive serological test for Bartonella henselae was received. In view of this result, a diagnosis of endocarditis was made, based on fulfilment of five Duke minor criteria, namely fever, predisposition, arterial emboli, immunological phenomena and serological evidence of active infection with an organism consistent with infective endocarditis. Immunosuppressive treatment was withheld and antibiotic treatment initiated. This case report emphasises the need for maintaining a high index of suspicion regarding the diagnosis of Bartonella infection, which might mimic ANCA-associated GN.